Aspek Kriminologis Tentang Peranan Masyarakat Dalam Pengendalian Sosial Di Desa Sekarwangi Kecamatan Cibadak Kabupaten Sukabumi - Yana Kusnadi Srijadi; Iwan Abadi; Iskandar Zulkarnaen; Eskar Tri Denatara; Anik Budiati; Juli Nurani; Triana Sunjaya; Steven Endrow (Jurnal Kajian Ilmiah, 2023)
In social control, society plays a crucial role in preventing crime and ensuring criminal justice. To explain the phenomenon of crime, there are three schools of thought in criminology: classical criminology, positivism, and critical criminology. Crime is viewed as a social problem that can be understood not only from a legal perspective but also through scientific study. Sanctions are a normative aspect of the social control system, and sociologically, they cannot be equated from one region to another. The potential for social control of crime can be achieved through problem-oriented policing and community policing by analyzing various aspects related to public satisfaction with the performance and quality of police services. The way society responds to various criminal acts can be studied from criminological and sociological perspectives, and the role of judges in dealing with offenders is essentially one form of social control by society.